2005
DOI: 10.1007/s10713-005-4676-1
|View full text |Cite
|
Sign up to set email alerts
|

Wealth Effects on Self-Insurance and Self-Protection against Monetary and Nonmonetary Losses

Abstract: This paper considers the wealth effects on self-insurance and self-protection activities against possible losses of monetary wealth such as properties and nonmonetary wealth such as health. Increased initial income or monetary wealth decreases the demand for self-insurance against monetary wealth loss under the decreasing absolute risk aversion assumption, and has an ambiguous effect on self-protection. However, increased initial monetary wealth increases both self-insurance and self-protection against health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Although there are many theoretical works about this issue (e.g., Immordino, ; Quiggin, ; Lee, ; Lohse et al ., ), we are aware of only two experimental studies that compared the individual valuations of SISP. Shogren (), for instance, concluded that a risk‐averse or risk‐neutral individual would value self‐protection more highly than self‐insurance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are many theoretical works about this issue (e.g., Immordino, ; Quiggin, ; Lee, ; Lohse et al ., ), we are aware of only two experimental studies that compared the individual valuations of SISP. Shogren (), for instance, concluded that a risk‐averse or risk‐neutral individual would value self‐protection more highly than self‐insurance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in many theoretical studies, a more risk-averse person was found to always invest more in self-insurance, but not necessarily more in self-protection (Dionne and Eeckhoudt, 1985;Briys and Schlesinger, 1990;Briys et al, 1991;Alary et al, 2013). As about the ambiguity effect on SISP, Snow (2011) shows that ambiguity averse individual value both self-insurance and selfprotection higher than the individuals that are not ambiguity averse, in addition, the valuation increases as the ambiguity aversion increases.Although there are many theoretical works about this issue (e.g., Immordino, 2000;Quiggin, 2002;Lee, 2005;Lohse et al, 2007), we are aware of only two experimental studies that compared the individual valuations of SISP. Shogren (1990), for instance, concluded that a riskaverse or risk-neutral individual would value self-protection more highly than self-insurance.…”
mentioning
confidence: 99%
“…Innym byłoby rozważenie przypadku wielu stanów świata, gdyż istniejąca do tej pory analiza teoretyczna ogranicza się tylko do dwóch stanów. Wymaga to jednak poważnego uogólnienia modelu, zaś niektóre wyniki mogą się okazać jakościowo odmienne od dotychczasowych, jak to pokazał Lee (2005) w pracy na temat efektu dochodowego w przypadku samoubezpieczenia (SI). W niniejszej pracy zajmujemy się problemem wyboru prawnika poprzez zastosowanie modelu stanowiącego połączenie samoubezpieczenia i prewencji (SICP) w sytuacji możliwości zwrotu kosztów w razie wygranej sprawy w sądzie.…”
Section: Po Przekształceniu Otrzymujemyunclassified
“…Sweeney and Beard (1992) and Lee (2005) analyze the wealth effects on self-protection, and on self-insurance, respectively, in a two-state model. But the wealth effects on self-insurance with multiple states have not been studied.…”
Section: Introductionmentioning
confidence: 99%